Prevalence and correlates of ICD-11-based prolonged grief disorder in a representative Slovakian sample of recently bereaved adults - Boelen, Paul A; Adamkovič, Matúš (European journal of psychotraumatology, 2024)
Background: Prolonged Grief Disorder (PGD) has recently been included in both the ICD-11 and DSM-5-TR diagnostic manuals. Studying its prevalence and correlates across cultures is vital for more effective identification, treatment, and prevention.Objective: This study aimed to examine prevalence rates of ICD-11-based PGD, in a representative Slovakian sample in response to deaths of loved ones occurring during the previous year. Further aims were to examine the factor structure of PGD symptoms and correlates of summed PGD item scores and PGD 'caseness'.Method: Self-reported data on PGD, depression, anxiety, alcohol use, and descriptive characteristics were gathered from a representative sample of the Slovak population (N = 319).Results: Data were gathered from N = 1853 people; 319 participants (17.2%) reported a loss in the past year. The prevalence of probable PGD among these bereaved participants was 1.99% for recent losses (<6 months, n = 151) and 7.75% for more distant losses (6-12 months, n = 130). The most frequently endorsed symptoms included longing/yearning for the deceased, sadness, denial/unrealness, and difficulty accepting the death. PGD symptoms had a unitary factor structure which was consistent for subsamples bereaved 1-5 and 6-12 months. The severity of PGD varied with kinship. Depression and anxiety, but not alcohol misuse, were associated with PGD severity and PGD caseness.Conclusions: These findings underscore that a significant group of people develop PGD between 6-12 months following a loss. This emphasises the need for targeted psychological interventions.
Keywords: Trastorno por duelo prolongado; Prevalence; zármutek; deprese; salud mental; mezinárodní klasifikace nemocí; Grief; Depression; International Classification of Diseases; Middle Aged; mužské pohlaví; prevalence; prevalencia; Adult; grief; bereavement; pérdida; mental health; Slovakia; Slovenská republika; ztráta blízké osoby; loss; ženské pohlaví; CIE-11; Humans; úzkost; Anxiety; Prolonged grief disorder; lidé středního věku; Bereavement; dospělí; Female; lidé; Male